Comparative studies of infectivity, immunogenicity and cross-protective efficacy of live attenuated influenza vaccines containing nucleoprotein from cold-adapted or wild-type influenza virus in a mouse model - Isakova-Sivak, Irina (Virology, 2016)
This study sought to improve an existing live attenuated influenza vaccine (LAIV) by including nucleoprotein (NP) from wild-type virus rather than master donor virus (MDV). H7N9 LAIV reassortants with 6:2 (NP from MDV) and 5:3 (NP from wild-type virus) genome compositions were compared with regard to their growth characteristics, induction of humoral and cellular immune responses in mice, and ability to protect mice against homologous and heterologous challenge viruses. Although, in general, the 6:2 reassortant induced greater cell-mediated immunity in C57BL6 mice than the 5:3 vaccine, mice immunized with the 5:3 LAIV were better protected against heterologous challenge. The 5:3 LAIV-induced CTLs also had better in vivo killing activity against target cells loaded with the NP(366) epitope of recent influenza viruses. Modification of the genome of reassortant vaccine viruses by incorporating the NP gene from wild-type viruses represents a simple strategy to improve the immunogenicity and cross-protection of influenza vaccines.